Trend and Momentum Technical Indicators for Investing in Market Indices - Padilha, Victor Alexandre; Magnani, Vinícius; Gatsios, Rafael Confetti; Guasti Lima, Fabiano; Moreira Antonio, Rafael (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2024)
The purpose of this study is to evaluate the effectiveness of technical analysis indicators in investment strategies.We conducted an empirical study using four trend indicators and four momentum indicators across seven market indices. Our methodology employs a parameter optimization process for each indicator and compares the results with classical parameters reported in the economics literature.Our findings indicate that no technical indicator consistently outperforms the buy-and-hold strategy in the long run. In addition, the optimization procedures did not yield significant improvements in the results.This study contributes to the ongoing debate on the effectiveness of technical analysis indicators in securities trading by adding to the literature on the subject.